17 beta-Hydroxy-17 alpha-(hydroxymethyl)estr-4-en-3-one - Yousuf, S.; Zafar, S.; Choudhary, M.I.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C19H28O3, the fungal-transformed metabolite of the steroid methyloestrenol contains four fused rings A, B, C and D. Ring A adopts a half-chair and the transfused rings B and C adopt chair confirmations; the five-membered D ring is folded like an envelope. In the crystal, adjacent molecules are linked by O-H center dot center dot center dot O-carbonyl and O-H center dot center dot center dot O-hydroxy hydrogen bonds into a layer structure.